Causal associations between chronic viral hepatitis and psychiatric disorders: a Mendelian randomization study - Fu, Haoshuang; Jiang, Shaowen; Song, Shuying; Zhang, Chenxi; Xie, Qing (Frontiers in Psychiatry, 2024)
There may be an interaction between viral hepatitis and psychiatric disorders during disease progression. Herein, we conducted Mendelian randomization (MR) to explore the causal associations and mediators between viral hepatitis and psychiatric disorders. Genome-wide association studies summary data for viral hepatitis [including chronic hepatitis B (CHB) and chronic hepatitis C (CHC)] and psychiatric disorders (including depression, anxiety, schizophrenia, obsessive-compulsive disorder, bipolar disorder, and post-traumatic stress disorder) were obtained. Two-sample MR was performed to assess the causal associations between viral hepatitis and psychiatric disorders. Further, 0.00%-1.70%) proportion, respectively. We revealed that schizophrenia patients faced a high risk of CHC, and insufficient coffee consumption and underweight could mediate the causal effect of schizophrenia on CHC. The prevention of hepatitis C might be a beneficial strategy for patients with schizophrenia. The right amount of nutrition supplements and coffee consumption might be part of a beneficial lifestyle in preventing the high CHC risk in patients with schizophrenia.